THE EFFECTIVENESS OF USING ROLE PLAY STATEGY TO TEACH SPEAKING (A PRE-ECPERIMENTAL STUDY AT CLASS VIII A OF SMPN 1 JOMBANG): The effectiveness of using role play stategy to teach speaking (a pre-ecperimental study at class VIII a of smpn 1 jombang - Mesy Fauzya; Mukminatus Zukhriyah (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This study intends to ascertain whether students' speaking abilities have improved both before and after being instructed utilizing a role-playing technique. A pre-experimental design is employed. This study was carried out at SMPN 1 Jombang. Students in class VIII-A at SMPN 1 Jombang during the academic year 2022–2023 served as the study's samples. Through SPSS V.25, the researcher ran a t-test to assess the data. Pre-test and post-test scores were obtained by the researcher after data collection. The average pre-test score was 43.91, while the average post-test score was 52.08. The researcher then used the t test to assess the data, with a Sig. (2-tailed) result lower than 0.05. Ha is seen as acceptable, it can be said. Several conclusions were drawn from the data analysis, including that there were considerable variations between students and that the students' speaking abilities before and after employing a role-playing technique for instruction were still less obvious. Before and after employing role-playing techniques to teach speaking abilities. Thus, it can be said that the role-playing technique works well for enhancing speaking abilities in SMPN 1 Jombang pupils in class VIII-A.